2016
DOI: 10.1007/s10935-016-0448-1
|View full text |Cite
|
Sign up to set email alerts
|

Web-Based Prevention of Parenting Difficulties in Young, Urban Mothers Enrolled in Post-Secondary Education

Abstract: Research consistently indicates that young mothers are at elevated risk for adverse social and economic risks. Recent attention has been paid to the value of maternal educational attainment for their children's economic and social outcomes. Pursuit of post-secondary education requires mothers to balance multiple roles, potentially stressing the parent-child relationship. Yet, almost no studies have addressed parenting and associated stress in young mothers enrolled in post-secondary education, and no preventiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 38 publications
3
21
0
Order By: Relevance
“…For the RCTs, we utilized means and standard deviations of each group for pre-and post-scores. One RCT (Ehrensaft et al 2016) did not provide pre-intervention data, thus postintervention means and standard deviations were used. For pre-post designs, pre-and post-treatment means and standard deviations were extracted and a standardized difference score was calculated and corrected for bias in the calculation of g. Correlations between pre-and post-test scores, necessary to the calculation of pre-post effect size (Borenstein et al 2009), were provided in only three articles (Hudson et al 2012;Lipman et al 2011;Love et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the RCTs, we utilized means and standard deviations of each group for pre-and post-scores. One RCT (Ehrensaft et al 2016) did not provide pre-intervention data, thus postintervention means and standard deviations were used. For pre-post designs, pre-and post-treatment means and standard deviations were extracted and a standardized difference score was calculated and corrected for bias in the calculation of g. Correlations between pre-and post-test scores, necessary to the calculation of pre-post effect size (Borenstein et al 2009), were provided in only three articles (Hudson et al 2012;Lipman et al 2011;Love et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…One intervention was primarily delivered online, and An "x" indicates that the criterion has been met provided personalized support through a weekly telephone coach call and the ability to send emails to the coach (Baggett et al 2010). Four interventions did not include direct contact with an interventionist, and were delivered on a computer or tablet (Breitenstein et al 2016;Ehrensaft et al 2016;Hudson et al 2012;Love et al 2016). These interventions used websites or apps that included features such as video examples, knowledge questions to assess understanding, and online discussion forums for communication with other participants.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Numerous remotely-delivered intervention programs targeting parenting stress have been designed and tested, mostly within the context of caregivers of children with a diagnosed health condition [ 65 , 66 ]. Prevention programs that focus on parenting stress and that can be disseminated remotely [ 67 ] might serve as especially relevant foundations for pandemic-specific programs for caregivers experiencing stress during the COVID-19 crisis, as this appears to be a c-oncern among caregivers in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…They used several methods to acquire knowledge and skills, but they preferred virtual space and computer technology because of their interest. The success of this approach as a strategy - adopted by adolescent mothers and health care providers - has been endorsed in numerous studies ( 18 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Teenage mothers must be able to cope with the challenges. According to the results of studies, teenage mothers use several strategies for success in the maternal role these can be in the form of resilience ( 14 , 15 ), reinforcement of adaptive power, positive thinking, self-efficacy ( 16 ), restarting and establishing supportive relationships ( 17 ), and technology-based instruction ( 18 20 ). In addition, researchers have shown that health services ( 12 , 21 , 22 ), social support ( 3 , 10 , 12 ), financial support, removal of stigma, and cultural support ( 23 ) helps teenage mothers to success in the maternal role.…”
Section: Introductionmentioning
confidence: 99%